2014
DOI: 10.1186/1471-2334-14-93
|View full text |Cite
|
Sign up to set email alerts
|

TB incidence and characteristics in the remote gulf province of Papua New Guinea: a prospective study

Abstract: BackgroundThe incidence and characteristics of tuberculosis (TB) in remote areas of Papua New Guinea (PNG) are largely unknown. The purpose of our study was to determine the incidence of TB in the Gulf Province of PNG and describe disease characteristics, co-morbidities and drug resistance profiles that could impact on disease outcomes and transmission.MethodsBetween March 2012 and June 2012, we prospectively collected data on 274 patients presenting to Kikori Hospital with a presumptive diagnosis of TB, and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…However, a similar TB burden might also occur in more moderate HIV burden settings, when considering smaller subnational populations or local communities such as PNG-GP within countries of much lower national incidence 17. Our results suggest that it is only when incidence reaches extremely high levels (>1400 cases/100 000/year) that the effects of IPT begin to attenuate.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, a similar TB burden might also occur in more moderate HIV burden settings, when considering smaller subnational populations or local communities such as PNG-GP within countries of much lower national incidence 17. Our results suggest that it is only when incidence reaches extremely high levels (>1400 cases/100 000/year) that the effects of IPT begin to attenuate.…”
Section: Discussionmentioning
confidence: 58%
“…Four examples of countries/region are represented in Figure 2 to illustrate different levels of TB incidence: Micronesia (MIC), Cambodia (CAM), Kiribati (KIR) and the Gulf Province of Papua New Guinea (PNG-GP), with estimated TB incidences of respectively 195, 390, 497 and 1290 cases per 100 000 population per year 1,17. As our baseline analysis does not apply to HIV-endemic settings, only settings with low HIV prevalence are presented.…”
Section: Resultsmentioning
confidence: 99%
“…In 2014, the WHO estimate of incidence was 417 cases per 100,000 people, with multidrug resistance estimated at 2.7% in new cases, and 19% in retreatment cases [4]. However, region-specific studies in PNG have suggested higher rates of TB and drug resistance, with incidence estimates of 550–1290 cases per 100,000 people, and multidrug resistance in 5–25% of patients [510]. …”
Section: Introductionmentioning
confidence: 99%
“…The official estimate of tuberculosis incidence in PNG in 2015 was 432 per 100,000 31 . This is likely an under‐estimate, and notification rates of 1,000 per 100,000 were observed when measured accurately and systematically in the Gulf Province 32 …”
Section: Exotic Pathogen Risks For Australia Through the Indo‐papuan mentioning
confidence: 97%